UiTM TESL students' perspective towards the integration of blended learning in their studies / Raja Rosemawati Raja Abdullah - Raja Abdullah, Raja Rosemawati (Faculty of Education, 2014)
Teaching is never an easy job, especially in this modern world where technology rules almost everything. Thus, education has to adapt with this changes. The education sector was previously introduced to e-learning but recently, the term blended learning was introduced to teaching field. Tertiary education institutions are applying this method of teaching in their education system However, this method have yet to win the favour of all educators and students involved. Thus, this research is aiming to find out the students' perspective towards this method of teaching. Other than that, this paper is investigating the preferable medium to use in study. Lastly, researcher wants to identify the problems and issues laced in incorporating blended learning. Nevertheless, the results obtained do not agree with the expectations. Although the participants have a positive perspective towards blended learning but they do not prefer to incorporate blended learning in their studies. Thus, in order to chance the students' preference, teachers and academic stalls have to find better solution to encounter all the problems and issues lace during conducting blended learning.